1979
DOI: 10.1139/o79-107
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among purine nucleoside metabolism, adenosine triphosphate catabolism, and glycolysis in human erythrocytes

Abstract: In human erythrocytes incubated with both naturally occurring purine nucleosides and with a variety of purine nucleoside analogs, ATP catabolism was accelerated and lactate accumulation was increased. Tubercidin was a particularly potent inducer of ATP catabolism. In cells incubated with tubercidin, the major route of adenylate metabolism was deamination, whereas in cells incubated with deoxyglucose, the major pathway was dephosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…In mature erythrocytes, even more than in other cell types, adenine nucleotides constitute the most abundant nucleotide compounds. 5'-Nucleotidase(s) intervene(s) in their catabolism by dephosphorylating either AMP or its deamination product IMP, depending on the experimental conditions [6][7][8][9]. Yet the precise identity of the enzyme(s) responsible for this process has not been determined with certainty.…”
Section: Introductionmentioning
confidence: 99%
“…In mature erythrocytes, even more than in other cell types, adenine nucleotides constitute the most abundant nucleotide compounds. 5'-Nucleotidase(s) intervene(s) in their catabolism by dephosphorylating either AMP or its deamination product IMP, depending on the experimental conditions [6][7][8][9]. Yet the precise identity of the enzyme(s) responsible for this process has not been determined with certainty.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of both enzymes should produce accumulation of adenosine. A few studies have assessed the involvement of deamination and dephosphorylation of AMP in the breakdown of erythrocytic ATP induced by various drugs and metabolic inhibitors (9,10). The catabolism of the adenine nucleotides under physiologic conditions and its acceleration provoked by lack of glucose (1 1), alkalinization of the medium (12,13), and depletion of Pi (14)(15)(16) have, however, not been investigated in this respect, nor has the possibility of a recycling of adenosine been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Both NH( and Pi may exert their effect on ATP and DPG metabolism by several mechanisms. It is known that NH4 has a stimulatory action on the pentose phosphate pathway [20][21][22][23], This may result in the increased formation of phosphoribosylpyrophosphate (PRPP) which is needed for the phosphorylation of ade nine by adenine phsophoribosyltransferase [24]. Kay and Beutler [4] found that the activity of APRT was unaffected by ammonium ions.…”
Section: Discussionmentioning
confidence: 99%